2022
DOI: 10.3390/ijerph191710675
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development Goals Psychological Inventory: A Network Analysis in Italian University Students

Abstract: The Sustainable Development Goals Psychological Inventory (SDGPI) is a recently developed self-report questionnaire that assesses interest, motivation, and self-efficacy associated with each of the 17 Sustainable Development Goals (SDGs) advanced by the United Nations. This study aims to investigate, via network analysis, (a) the relationships between interest, motivation, and self-efficacy for each SDG and (b) the most central SDGs. To this end, 417 Italian university students (73.9% females and 26.1% males; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The recently developed Sustainable Development Goals Psychological Inventory (SDGPI) may be a starting point for vocational practitioners when working with job seekers entering the workforce or individuals looking to switch careers. The SDGPI is designed to assess the individual's perceptions and determine the importance of the 17 SDGs 8 through a focus on three psychological aspects – interest, motivation, and self-efficacy (Di Fabio & Rosen, 2020; Svicher et al, 2022). The O*NET taxonomy now lists more than 60 occupations that incorporate environmental aspects into the required knowledge and skills required in job performance (Dierdorff, 2013).…”
Section: Job-seeking and Vocational Psychologymentioning
confidence: 99%
“…The recently developed Sustainable Development Goals Psychological Inventory (SDGPI) may be a starting point for vocational practitioners when working with job seekers entering the workforce or individuals looking to switch careers. The SDGPI is designed to assess the individual's perceptions and determine the importance of the 17 SDGs 8 through a focus on three psychological aspects – interest, motivation, and self-efficacy (Di Fabio & Rosen, 2020; Svicher et al, 2022). The O*NET taxonomy now lists more than 60 occupations that incorporate environmental aspects into the required knowledge and skills required in job performance (Dierdorff, 2013).…”
Section: Job-seeking and Vocational Psychologymentioning
confidence: 99%
“…Therefore, motivation is collected as a key element of study to investigate the relationship between university students and concern for well-being. This can be appreciated in the research by Svicher et al [10] about a self-report that evaluates the interest, motivation, and self-efficacy associated with each of the SDGs in Italian university students or in the research by Kinoshita et al [11] on the development of an educational program for university students focused on the motivation for sustainability. The results of both investigations showed that students with higher levels of intrinsic and extrinsic motivation tended to use more effective learning strategies and are able to recognize their capacity to learn in order to generate and to make policy decisions through discourses that articulate and sustain good practices.…”
Section: Introductionmentioning
confidence: 99%